KONSEP MEMAAFKAN DALAM MENENANGKAN JIWA REMAJA DARI KELUARGA BROKEN HOME - St. Hajrah Syam; Rahmatullah Rahmatullah; Nensi Ratnasari; Nuraisyah Nuraisyah (Institut Agama Islam Muhammadiyah Sinjai, 2023)
Adolescence is a period of inner conflict for many individuals because it is during this period that many adolescents seek identity. In addition, they also have a high curiosity, so that coaching and guidance from family members and those closest to them, especially parents, is very important to guide teenagers to carry out positive and useful activities. But unfortunately, many teenagers find themselves in precarious situations, with broken families, or rather, with broken families. This study aims to find out what a broken home is, and to find out how the concept of forgiveness in calming the souls of teenagers from broken home families. In this study, researchers used library research, which is research that includes a series of activities related to library data collection methods. The results of this study explain that forgiveness in calming the souls of teenagers and broken home families is very important for teenagers